La rétinopathie de Valsalva et le travail d’accouchement au CHU-IOTA - M, SISSOKO; Ibrahima, CONARE; Nouhoum, GUIROU; Gounon, SAYE; Brainima, COULIBALY; Adama, GUINDO; Abdoulaye, NAPO; Fatoumata, SYLLA (Jour Med Resh and Health Sci, 2021)
Valsal va retinopathy occurs when superficial retinal capillaries are disrupted due to intraocular hyperpressure following a sudden increase in intrathoracic or intra-abdominal pressure. One patient of 24 had a sudden drop in visual acuity in her left eye during labor. The yag laser hyaloidotomy allowed a complete resorption of the haemorrhage and a clear improvement of visual acuity. The closed glottis push technique or vasalva maneuver during labor seems to be a risk factor for pre-retinal haemorrhage.